Strategic outsourcing in the German engine building industry: An empirical study based on the resource dependence approach - Susanne Gretzinger (Management Revue, 2008)
Outsourcing is an organizational measure that changes the resource dependencies of a company. In this paper, a framework is developed from the perspective of the resource dependence approach to explain strategic outsourcing in the German engine building industry. On the basis of the NIFA panel, which describes the development of this industry in the 1990s, the framework is examined in cross-sectional and longitudinal studies. It can be shown that the resource dependence perspective contributes to an explanation of organizational changes, both outsourcing and insourcing. In addition, the longitudinal studies show the significance of the strategic, that is, long-term orientation of the ensemble of organizational measures towards company success.
Keywords: 650; Outsourcing; engine building industry; resource dependence approach; panel study